Magic Tree House: Merlin Mission - A Crazy Day with Cobras - Book 45 (17) - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2011)
The magic tree house whisks Jack and Annie to India during the Mogul Empire in the 1600s to search for an emerald needed to break a magic spell.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Time travel -- Fiction; Tree houses -- Fiction; Magic -- Fiction; Siblings -- Fiction; India -- Fiction -- History -- 1000-1765